La Lexicographie Scolaire comme Fondement de la Lexicographie Moderne au Gabon - Ella, Edgard Maillard (Lexikos, 2025)
School Lexicography as the Foundation of Modern Lexicography in Gabon. There is a close connection between lexicographic resources and the standardization process of languages for which reliable data is available. School lexicography thus plays an essential role in the standardization of French. With reference to the French model, we show the need to prioritize school lexicography as a foundation of modern lexicography of the local languages in Gabon. The process of standardization of local languages will be the corollary. Bilingual school dictionaries of French and these local languages constitute the type of work to be compiled in this priority order. This article refers exclusively to Boulanger (2006) who demonstrated the essential role of school lexicography in the standardization process of French. Keywords: bilingual school dictionaries, former lexicography, modern lexicography, school lexicography, standardization